ASSESSMENT OF GROUNDWATER QUALITY FOR DRINKING IN TUZ KHURMATU AREA, SALAHADDEN GOVERNORATE – IRAQ - Arjan Ali Rashid; Moutaz A. Al-Dabbas; Weam H. Kadhim (Iraqi Geological Journal, 2016)
The results of climatic data that obtained from Tuz Khurmatu meteorological station show actual evidence in the climatic changes, which are indicated by remarkable decreases in the means of annual rainfall, relative humidity percentages and with increases of the means of annual minimum and maximum temperatures. The unconfined aquifer of Adaim river basin is recharged mainly from rain water. Since this source is scarce, the aquifer gains its water slowly in a rate less than the rate of losing by both evaporation and abstraction wells. The water Quality Index (WQI) has been used to assess suitability of groundwater quality for human drinking purpose in Tuz Khurmatu area. Groundwater samples were collected in September (2010) and March (2011) from twenty wells and analyzed for their physicochemical characteristics such as pH, total dissolved solids, Electrical Conductivity, sodium, calcium, magnesium, potassium, bicarbonate, sulphate, chloride and nitrate. Each parameter was compared with its standard permissible limit as prescribed by Iraqi drinking water standards. The results showed that WQI values for the groundwater of the study area ranged from 27.25 to 139.81. Based on the WQI classification majority of the samples are falling under excellent to good water category and suitable for drinking water purpose.